Approximate Controllability of Fractional Sobolev-Type Evolution Equations in Banach Spaces - Mahmudov, N. I. (Hindawi Publishing Corporation, 2013)
We discuss the approximate controllability of semilinear fractional Sobolev-type differential system under the assumption that the corresponding linear system is approximately controllable. Using Schauder fixed point theorem, fractional calculus and methods of controllability theory, a new set of sufficient conditions for approximate controllability of fractional Sobolev-type differential equations, are formulated and proved. We show that our result has no analogue for the concept of complete controllability. The results of the paper are generalization and continuation of the recent results on this issue.
Keywords: Differential-Equations; Stochastic-Systems; Integrodifferential-Systems; Delay